Estimate Anti-symmetrical Divergence Modes of an Aircraft Wing Utilizing Aero-structure Analysis via Aerodynamic Lifting Line Theory - Abdalsalam Awadalla Ali Haj Ahmed (Engineering And Technology Journal, 2024)
This work illustrates the use of numerical matrix iteration to determine an aircraft wing’s divergence speed using the aerodynamic span effects. The work starts with the construction of equilibrium equations in differential and integral forms. In this paper, integral formulas are used because they provide a convenient basis for numerical solutions of complex practical problems. Second, the straight-tapered wing has been divided into a number of Multhopp stations. Subsequently, the stations’ torsional influence coefficient matrix has been calculated. Third, lifting line theory was used as a suitable choice of aerodynamic theory, and the governing equations were represented in matrix form. Finally, aerodynamic span effects are taken into consideration with induction effects according to Prandtl’s lifting line theory to calculate the anti-symmetrical divergence speed from the lowest eigenvalue of the homogenous governing integral equation. To get the solution to converge, a matrix has been iterated via the MATLAB program.